2012
DOI: 10.1371/journal.pone.0048870
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in DRBD3 Ribonucleoprotein Complexes in Response to Stress in Trypanosoma brucei

Abstract: Regulation of RNA polymerase II transcription initiation is apparently absent in trypanosomes. Instead, these eukaryotes control gene expression mainly at the post-transcriptional level. Regulation is exerted through the action of numerous RNA-binding proteins that modulate mRNA processing, turnover, translation and localization. In this work we show that the RNA-binding protein DRBD3 resides in the cytoplasm, but localizes to the nucleus upon oxidative challenge and to stress granules under starvation conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…Taken together, these findings indicate that Tc DRBD4/PTB2 is excluded from polysomes, as previously reported for T. brucei DRBD3 (Fernandez‐Moya et al. ), and suggest that Tc DRBD4/PTB2‐containing RNP complexes are not involved in translation events.…”
Section: Resultssupporting
confidence: 89%
“…Taken together, these findings indicate that Tc DRBD4/PTB2 is excluded from polysomes, as previously reported for T. brucei DRBD3 (Fernandez‐Moya et al. ), and suggest that Tc DRBD4/PTB2‐containing RNP complexes are not involved in translation events.…”
Section: Resultssupporting
confidence: 89%
“…The concept of RNA regulons, multiple mRNAs with a shared functional relationship, has been implicated in kinetoplastids (Zick et al 2005;Estévez 2008;Ouellette and Papadopoulou 2009;Queiroz et al 2009;Fernandez-Moya et al 2012). Notably, mammalian eIF4E is a central protein in an RNA regulon related to mRNA export and cell proliferation (Culjkovic et al 2005;Culjkovic et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several clusters of stress regulated transcripts were observed (as depicted in Table 5), denoting that potential RNA regulons can still coordinate gene expression under osmotic stress conditions. In this context, it was also shown that TbDRBD3 remains bound to its specific target transcripts after starvation or arsenite treatment (Fernandez-Moya et al, 2012). …”
Section: Discussionmentioning
confidence: 99%